KONSEP PENDIDIKAN AKHLAK DALAM NOVEL TRILOGI NEGERI 5 MENARA - Nazza Mufida Ansori (Lembaga Penerbitan dan Publikasi Ilmiah (LPPI) Universitas Muhamamdiyah Palopo, 2022)
The most important education in human life is moral education. In every human action, moral education is a benchmark in human daily life. The purpose of this research is to reveal Moral Education in the novel Trilogy Negeri 5 Menara (Adopsi Film by Ahmad Fuadi) published by PT. Gramedia Pustaka 2010. And the focus here is the concept of moral education contained in the novel Negeri 5 Menara. The research method used is a qualitative research method where the research procedure produces descriptive data in the form of written words and not numbers which are usually arranged into expanded text. The object of this research is a literary work in the type of novel, so this research is included in the type of manuscript research, this research relies on library research. The results of the study indicate that there is a concept of moral education in Ahmad Fuadi's novel, including: Morals to God, morality to humans consisting of morals to family, self and others.